DNA damage-triggered activation of cGAS-STING pathway induces apoptosis in human keratinocyte HaCaT cells. (March 2021) - Li, Can; Liu, Weiwei; Wang, Fang; Hayashi, Toshihiko; Mizuno, Kazunori; Hattori, Shunji; Fujisaki, Hitomi; Ikejima, Takashi
Graphical abstract: Highlights: UVB or cisplatin induces nuclear and mitochondrial DNA damages. UVB or cisplatin activates cGAS-STING pathway. STING knockdown inhibits apoptosis caused by UVB or cisplatin. cGAS-STING activates NF-κB and IRF3-IFNβ pathway leading to apoptosis. Abstract: Exposure to ultraviolet B (UVB) from sunlight causes DNA damage, serious cellular inflammation and aging, and even cell death in the skin, commonly known as sunburn, leading to cutaneous tissue disorders. DNA damage can be sensed as a danger-associated molecular pattern (DAMP) by the innate immune system. It has not been studied, however, whether cGAS-STING activation is involved in the apoptosis induced by UVB irradiation or by cisplatin treatment. Here we report the findings that within hours of DNA damages keratinocytes show an innate immune response, which involves the activation of cGAS-STING; a cytosolic DNA receptor, cGAS (cyclic guanosine monophosphate-adenosine monophosphate synthase), cyclic GMP-AMP (cGAMP) synthase, and DNA sensing adaptor, STING (protein stimulator of interferon genes). Either UVB irradiation or cisplatin treatment can cause DNA damages, releasing fragmented DNA from nucleus and/or mitochondria. Roles of cGAS-STING were examined in the HaCaT cells with DNA damages caused by UVB irradiation or cisplatin treatment. Silencing STING by siRNA rescued HaCaT cells from UVB or cisplatin-induced apoptosis. NF-κB, one of the major downstream components of STING pathway, which usually regulates the classical STING apoptotic pathway, was translocated to nucleus in the HaCaT cells irradiated with UVB. This translocation was attenuated by STING silencing. Treatment with BAY, an inhibitor of NF-κB pathway, blocked UVB-induced apoptosis. cGAS-STING-mediated production of IFNβ was induced by nuclear translocation of interferon regulatory factor 3 (IRF3). UVB irradiation inceased the nuclear translocation of IRF3, accompanied by enhanced expression level of IFNβ mRNA. The nuclear translocation of IRF3 and expression of IFNβ mRNA were attenuated by STING silencing. Treatment with MRT67307, an inhibitor of TBK1-IRF3-IFNβ pathway, blocked UVB-induced apoptosis. Therefore, we conclude that NF-κB pathway and IFNβ pathway residing in the downstream of STING are resposible for apoptosis of UVB-irradiated or cisplatin-treated HaCaT cells.